Economic and Social Impacts of Second-home Tourism on the Algarve Region - Luis N. PEREIRA; Daria VARTANOVA (Communications of International Proceedings, 2022)
This study aims to analyze the social and economic impacts of second-home tourism on the Algarve region, Portugal, as well as to characterize the main motivational factors that lead to the decision of choosing the Algarve as the main destination for second-home tourism. A survey was run to deductively explore tourists’ perceptions and experience owning a second-home in the Algarve. The research instrument was developed based on the questionnaire by Wong et al. (2014) and Marjavaara & Müller (2007) and the literature review of the works on similar topics in different countries around the world. Through an online-survey a sample of 300 tourists were interviewed in 2021. This study showed that second-home tourists generate a significant social impact on the Algarve, because the second-home tourists make friends with the local population, learn Portuguese, and cause the local population to adapt to their needs, while adapting to Portuguese customs. The main economic impacts included the high activity in the recreational, hotel and the real estate sector caused by the second-home tourists. Main motivations for choosing the Algarve as the second-home destination were the geographical proximity to the country of origin of second-home owners, mild climate, adapted infrastructure and wide usage of English.
Keywords: Second-home Tourism; Economic Impacts; Social Impacts; Motivational Factors.